EAGLE : ENVIRONMENTAL GEOGRAPHERS UNMANNED AERIAL VEHICLE SEBAGAI INOVASI PEMANFAATAN PESAWAT TANPA AWAK DAN PENGOLAHAN FOTO UDARA DIGITAL UNTUK PEMBUATAN PETA NAVIGASI PADA OLAHRAGA ORIENTEERING - Perdana, Ferdiyan Puja; Indriasari, Dewi; Hidayat, Ahmad Haidir; Pamungkas, Kartiko Gilang (Program Kreativitas Mahasiswa - Teknologi, 2013)
Orienteering is a kind of sport that requires navigational skill to use a map and compass well. In fact, availability of the navigation maps as important thing in Orienteering competitions, especially in Indonesia, not available enough, and that is one of problems the sport canât grow well in this country. EAGLE, Environmental Geographers Unmanned Aerial Vehicle, is an innovation that use of unmanned aerial vehicle to produce the digital aerial photography for making navigation map in the Orienteering sport as a solution to solve the problem that faced by partner.EAGLE has a sensor camera that equipped with accurate navigation and flight remote control system, and has data link communications system that continually able to transmit the plane status, targets and information of remote sensing with digital image format as real time. Furthermore, EAGLE has a lightweight that make it easy to do maneuver and practical to use. The digital aerial photography of EAGLE also allows for digital image processing and analysis of spatial to generate elevation information and spatial modeling. EAGLE is a long-term investment for availability remote sensing data as a solution for the problem that faced by the partner, Federasi Orienteering Nasional Indonesia, as a leader organization of orienteering sport in Indonesia.